Newborn Screening and Molecular Profile of Congenital Hypothyroidism in a Chinese Population - Yu, Bin; Long, Wei; Yang, Yuqi; Wang, Ying; Jiang, Lihua; Cai, Zhengmao; Wang, Huaiyan (Frontiers in Genetics, 2018)
To review the characteristics of newborn screening of congenital hypothyroidism (CH), we reviewed the newborn screening data, including the levels of blood spot thyroid-stimulating hormone (TSH), and serum TSH and free thyroxine (FT4), of all newborn infants who accepted the newborn screening program during the last 14 years. In total, 437,342 newborn infants underwent CH screening and 192 infants were diagnosed with CH and the incidence of CH was 1:2278. The positive rate of the initial screening was 0.96%, and the positive predictive value was 4.8%. We also designed a target sequencing panel including 13 causative genes: DUOX2, TG, TPO, TSHR, TTF1, TTF2, PAX8, NKX2-5, GNAS, THRA, TSHB, IYD and SLC5A5, to identify the spectrum and prevalence of disease-causing gene mutations in Chinese CH patients. CH-causing genes were detected by targeted next generation sequencing in 106 CH infants. A total of 132 mutations were identified in 69 cases (65.1%). Of these 132 mutations, 92 (69.70%), 28 (21.21%), and 12 (9.09%) were related to thyroid dyshormonogenesis, thyroid dysgenesis, and thyrotropin resistance, respectively. Mutations in CH-causing genes were found mainly in DUOX2, TG and TSHR, and DUOX2 is the most gene mutation in Chinese CH patients.